Successful treatment with acitretin in a case of ichthyosis epidermolytica. - Yordanova, I.; Trashlieva, M.; Angelova, L.; Koitchev, K. (European Journal of Pediatric Dermatology, 2000)
Ichthyosis epidermolytica (IE) is a rare form of ichthyosis, due to an inherited severe disturbance of the keratinization. We present a 6-year-old boy with IE. The disease started immediately after birth with vesicules and blisters all over the body, which ruptured spontaneously and healed without scars. Gradually, the skin scale surface became dry and covered by disagreeable smelling, yellow-greyish scales, under which inflamed erythematous skin appeared through. The disease affected the entire skin surface, being more severe on the articular regions. The histology examination revealed the pattern of epidermolytic hyperkeratosis. The electron microscopy examination showed “tonofilament clumps” perinuclearly and peripherally in the cells of the granular and upper prickly epidermal layers. Systemic therapy with acitretin in minimal dose and careful monitoring for side effects significantly improved the disease in our case.